Identification of important characters by principal component analysis in sesame germplasm: Identification of important characters by principal component analysis in sesame germplasm - MANASI DASH; SANDEEP KUMAR SINGH; BANSIDHAR PRADHAN (Journal of Oilseeds Research, 2020)
The objective of the present research was to identify superior sesame genotypes and important characters in order to explain their differences for further use in cultivar development program. Based on principal component analysis the first three principal components accounted for 65.93% of total variations. Among the nine morphological traits seed yield/plant, branches/plant, capsules/plant and plant height were greater contributors to variability. Hence in designing a hybridization program due weightage can be given to these four characters.